I looked at you, you looked at me, I smiled at you, you smiled at me—The impact of eye contact on emotional mimicry - Mauersberger, Heidi; Kastendieck, Till; Hess, Ursula (Frontiers in Psychology, 2022)
Eye contact is an essential element of human interaction and direct eye-gaze has been shown to have effects on a range of attentional and cognitive processes. Specifically, direct eye contact evokes a positive affective reaction. As such, it has been proposed that obstructed eye contact reduces emotional mimicry (i.e., the imitation of our counterpart's emotions). So far, emotional mimicry research has used averted-gaze faces or unnaturally covered eyes (with black censor bars) to analyze the effect of eye contact on emotional mimicry. However, averted gaze can also signal disinterest/ disengagement and censor bars obscure eye-adjacent areas as well and hence impede emotion recognition. In the present study (N = 44), we used a more ecological valid approach by showing photos of actors who expressed either happiness, sadness, anger or disgust while either wearing mirroring sunglasses that obstruct eye contact or clear glasses. The glasses covered only the direct eye region but not the brows, nose ridge and cheeks. Our results confirm that participants were equally accurate in recognizing the emotions of their counterparts in both conditions (sunglasses vs. glasses). Further, in line with our hypotheses, participants felt closer to the targets and mimicked affiliative emotions more intensely when their counterparts wore glasses instead of sunglasses. For antagonistic emotions, we found the opposite pattern: Disgust mimicry, which was interpreted as an affective reaction rather than genuine mimicry, could be only found in the sunglasses condition. It may be that obstructed eye contact increased the negative impression of disgusted facial expressions and hence the negative feelings disgust faces evoked. The present study provides further evidence for the notion that eye contact is an important prerequisite for emotional mimicry and hence for smooth and satisfying social interactions.